2008
DOI: 10.3989/revmetalm.2008.v44.i3.113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red mud in the electrochemical behaviour of carbon steel embedded in mortar

Abstract: El hormigón, debido a su elevada alcalinidad, protege al acero mediante la formación de una película pasiva que impide su corrosión. Sin embargo, la presencia de agentes agresivos (cloruros, sulfatos y dió-xido de carbono) a nivel de la interfase acero-hormigón puede causar la pérdida de pasividad del acero y crear condiciones favorables para el inicio de la corrosión de las armaduras. El estudio de los posibles inhibidores de corrosión en este medio resulta de vital importancia desde un punto de vista económi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Furthermore, those authors [31] also pointed out that with an increase in red mud content from 0% to 25%, the reduction in the quantities of CO, NO X , Pb and SO 2 is about 32.5%, 31.8%, 17.1% and 22.4% respectively. Finally, the relatively good behaviour of red mud regarding the resistance to chloride ingress observed here will be in line with other investigations [23][24][25][26][27], in which it has been shown that red mud has good performance in relation to the protection against corrosion of steel reinforcements embedded in concrete.…”
Section: Forced Migration Testsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, those authors [31] also pointed out that with an increase in red mud content from 0% to 25%, the reduction in the quantities of CO, NO X , Pb and SO 2 is about 32.5%, 31.8%, 17.1% and 22.4% respectively. Finally, the relatively good behaviour of red mud regarding the resistance to chloride ingress observed here will be in line with other investigations [23][24][25][26][27], in which it has been shown that red mud has good performance in relation to the protection against corrosion of steel reinforcements embedded in concrete.…”
Section: Forced Migration Testsupporting
confidence: 92%
“…In relation to the use of red mud in cement-based materials, considering its composition, it is possible that it has pozzolanic activity and some research has pointed out this possibility [21,22]. Along this line, there are several dispersed works related to the use of this addition in those materials and some of them have shown that red mud seems to improve protection against corrosion of reinforcements embedded in concrete [23][24][25][26], as well as the transport properties of cement-based materials [27]. In addition to this, there are also some recent studies in which the mechanical strengths of cementitious materials with red mud have been analysed.…”
Section: Introductionmentioning
confidence: 99%